The Relationship Between Childhood Traumatic Experiences and Obsessive Beliefs in Alcohol Use Disorder - Fatma Gül Helvacı Çelik; Seda Kiraz (Hitit Medical Journal, 2023)
Objective: Based on the pathophysiological similarities between alcohol use disorder (AUD) and obsessive compulsive spectrum disorders, as well as the close association between traumatic experiences and addiction, the goal of this study was to assess the relationship between obsessive beliefs and childhood traumas in patients with alcohol use disorder by comparing them with the control group. Material and Method: The data of 60 AUD cases who applied to the Alcohol and Substance Treatment Center (AMATEM) outpatient clinic consecutively and 56 healthy control groups were evaluated. Structured Clinical Interview for DSM-5 (SCID-5), Obsessive Beliefs Questionnaire (OBS), Childhood Trauma Questionnaire (CTS), Hamilton Anxiety Inventory (HAM-A), and Hamilton Depression Inventory (HAM-D) were applied to both groups. The Addiction Profile Index, which evaluates the severity of addiction, was applied to the patient group. Data were evaluated with SPPS 22. Results: Obsessive beliefs, traumatic experiences, depression and anxiety scores were found to be significantly higher in AUD cases than in the control group. No significant relationship was found between traumatic experiences and obsessive beliefs. The most important predictors of obsessive beliefs were found to be anxiety and depression scores. Conclusion: The current study is valuable because it is the first study to evaluate the relationship between obsessive beliefs and childhood traumas in alcohol use disorder patients. Further analyzes in a larger sample in this area will be helpful in identifying risk factors and creating preventive interventions for AUD, a disorder that is difficult to treat and recurs.